Depression Symptoms Are Associated with Poor Functional Status Among Operative Spinal Deformity Patients. Issue 7 (1st April 2021) - Lafage, Renaud; Ang, Bryan; Schwab, Frank; Kim, Han Jo; Smith, Justin S.; Shaffrey, Christopher; Burton, Douglas; Ames, Christopher; Mundis, Gregory; Hostin, Richard; Bess, Shay; Klineberg, Eric; et al.
Abstract : Study Design: Retrospective review of prospective multicenter database. Objective: The aim of this study was to investigate how preoperative mental status affects preoperative and postoperative disability and health scores in adult spinal deformity (ASD) patients. Summary of Background Data: The relationship between health-related quality of life (HRQOL) and depression has previously been documented. However, the influence of depression on clinical outcomes among ASD patients is not well understood. Methods: ASD patients with minimum 2-year follow-up were stratified based on preoperative mental health measured by Short Form 36 (SF-36) mental component score (MCS). Patients with MCS in the 25 th and 75 th percentile of the cohort were designated as having low and high MCS, respectively. After matching by preoperative demographics and deformity, pre- and post-HRQOL were compared between the two groups. Further analysis was performed to identify individualized questions on the SF-36 that could potentially screen for patients with low MCS. Results: Five hundred thirteen patients were assessed (58.4 years' old, 79% women, mean MCS 45.5). Thresholds for low and high MCS cohorts were 35.0 and 57.3, respectively. After matching by preoperative alignment, low MCS patients had worse Oswestry Disability Index (ODI) (52.3 ± 17.0 vs. 35.7 ± 14.6, P  < 0.001) and Scoliosis Research Society-22R scores for all domains (all P  < 0.001) compared to high MCS patients. Similar results were maintained at 2-year postop, with low MCS patients having a worse ODI (35.2 ± 20.2 vs. 19.7 ± 18.6, P  < 0.001) and MCS (42.4 ± 13.5 vs. 58.6 ± 7.1, P  < 0.001). Despite similar preoperative Physical Component Score (PCS), low MCS patients were less likely to reach MCID for PCS (46.1% vs. 70.6%, P  < 0.01) and had a lower satisfaction at 2-year follow-up (3.88 ± 1.07 vs. 4.39 ± 0.94, P  < 0.001). Questions 5a, 9d, and 9f on the SF-36 were found to be independent predictors of low MCS. Conclusion: ASD patients with low MCS are more likely to experience functional limitations before and after surgery and are less likely to be satisfied postoperatively, even when similar clinical goals are achieved. Incorporating psychological factors may assist in decision making. Level of Evidence: 3